Influence of customer engagement with company social networks on stickiness: Mediating effect of customer value creation. Issue 3 (June 2017) - Zhang, Mingli; Guo, Lingyun; Hu, Mu; Liu, Wenhua
Highlights: Customer engagement on CSN comprises three dimensions: conscious participation, enthusiasm, social interaction. Customer engagement has a direct and significant influence on stickiness. Customer value co-creation mediates the relationship between customer engagement and stickiness. CSN managers should take actions to strengthen customer engagement for better business promotion. Abstract: Company social networks have become an important means for the socialized marketing of a company, forming a new challenge to companies on how to attract customers. Based on such theories as customer engagement, value co-creation, and relationship marketing, this paper presents a model of the influence of customer engagement on stickiness. Data collected from 260 valid questionnaires from Sina's enterprise microblog users were analyzed by structural equation modeling. Empirical results show that customer engagement has a direct and positive influence on customer stickiness as well as an indirect influence through customer value creation. This study enriches previous researches on existing theories of customer engagement, value co-creation, and stickiness, and gives practical guidance for companies to encourage customer engagement and enhance the stickiness of company social networks.